The Effect of Information Technology Governance and Enterprise Risk Management on the Performance of State-Owned Enterprises in Non-Public Financial Fields Moderated by Corporate Governance - Mochamad Muslih; Iis Sugianti; Daulat Freddy Simanjuntak; Dedi Rianto Rahadi (GoAcademica Research & Publishing, 2020)
The use of information technology is a necessity and a challenge in this 4th-millennium era. Companies that do not want to use technology that suits their needs will be left behind. The Indonesian government has also required the use of appropriate information technology. The purpose of this study is to evaluate the implementation of the Ministry of SOE Regulation No. Per 02 / MBU / 2013 concerning guidelines for the preparation of information technology management of State-Owned Enterprises (SOE) in the field of non-public finance and the implementation of risk management to SOEs that are moderated by corporate governance. The population in this study is State-Owned Enterprises (SOE) in the financial sector. The research sample of 17 SOEs was sampled with the purposive sampling method. The analysis technique used is multiple linear regression. The results showed that IT Governance does not affect firm performance. ERM significantly influences firm performance. Corporate governance that is proxied by the number of audit committee meetings does not moderate IT governance's influence on firm performance and does not mild ERM's effect on firm performance.